The effect of consuming rosella flower-infused water on control blood pressure in pregnant women with hypertension - Amin, Dewita Rahmatul; Sugiarti, Rosi Kurnia (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Hypertension during pregnancy is one of the leading causes of maternal morbidity and mortality. Rosella flower infused-water, rich in bioactive compounds such as flavonoids and polyphenols, have been shown to lower blood pressure safely. Although previous studies have highlighted the antihypertensive effects of rosella in the general population, research specifically focusing on its use in pregnant women with hypertension is still limited. Objective: This study aims to investigate the effect of rosella flower-infused water on control blood pressure reduction in pregnant women with hypertension. Method: The research design used is quasi-experimental with a pre-test and post-test approach involving 100 pregnant women with hypertension in Desa Karangraharja. The intervention group received 200 ml of rosella flower-infused water for 14 days in conjunction with nifedipine 10 mg, while the control group only received nifedipine 10 mg. The blood pressure of the control and intervention groups was measured using the Mann-Whitney Test. Results: The rosella flower-infused water effectively reduced systolic blood pressure in the intervention group by 24.92 mmHg compared to the control group by 18.78 mmHg (p=0.000). Diastolic blood pressure in the intervention group decreased by three mmHg, although this was not statistically significant compared to the control group's decrease of 3.6 mmHg (p=0.715). Conclusion: The 200 ml rosella flower-infused water for 14 consecutive days reduced systolic blood pressure in pregnant women with hypertension.